ATOM dan MOLEKUL BERDASARKAN ILMU KIMIA DAN PERSPEKTIF AL-QURAN - Sabarni Sabarni (UIN AR-RANIRY, 2014)
Atoms and molecules in chemistry teaching in schools is usually not associated with a particular religion of the Qur'an, so as if the atoms and molecules that learning is a science that is separate and has no relations with Al-Quran. To show that the Koran is a guide for mankind, including studying the natural sciences including chemistry, the authors wanted to examine the problem of atoms and molecules based chemistry and the perspective of the Koran which aims to determine the understanding of atoms and molecules according to the concept chemical and Koran, aspects of what is contained in the Koran that can be used as a guide in the learning of atoms and molecules. Data collection techniques used in this study is a library (Library Research) is studying the Quran and studying reading books, journals, textbook, dictionary, and scientific works. From these studies show that the Koran was first explained the concept of atoms and molecules as well as parts and in the Koran there is the concept of atoms and molecules that are in line with the chemical concepts put forward by the chemist